What is 6/10 minus 6/9?
Looking for the result of 6/10 - 6/9? Follow this step-by-step guide to understand how to subtract these two fractions.
How to subtract 6/10 by 6/9?
- Multiply the numerator of the first term, with the denominator of the second term: 6 × 9 = 54
- Multiply the numerator of the second term, with the denominator of the first term: 6 × 10 = 60
- Subtract both of these results together to form the new numerator: 54 − 60 = -6
- Multiply both denominators together to form the new denominator: 10 × 9 = 90
- Combine the results to get the new fraction: -6/90
- Simplify the fraction (-6/90) by dividing both the numerator and the denominator by their GCD (6):
- -6/6 = -1
- 90/6 = 15
- This gives: -1/15.
The result of subtracting 6/10 and 6/9 is : -1/15 (or -0.066666666666667 in its decimal form)